Making transcendents: ascetics and social memory in early medieval China - Campany, Robert Ford (University of Hawai'i Press, 2017)
Bringing transcendents down to earth -- The transcendent's cultural repertoire -- Deeper repertoire analysis: "avoiding grains" -- Secret arts, manifest wonders -- Verbal self-presentation and audience response -- Adepts and their communities -- Adepts, their families, and the imperium -- Hagiographic persuasions.